Factors associated with acute malnutrition among children 6‐59 months in rural Mozambique. Issue 1 (17th July 2020) - Zaba, Tomás; Buene, Dino; Famba, Elda; Joyeux, Mathieu
Abstract: Factors associated with acute malnutrition are complex and wide‐ranging particularly in developing countries. In Mozambique, contextual factors associated to children acute malnutrition are yet to be fully investigated and the evidences used to better inform prevention programme. The objective of this study is to identify key factors associated with acute malnutrition among 6‐ to 59‐month‐old children living in nine districts in rural Mozambique assessed in the 2018 seasonal nutrition assessment. We analysed Standardized Monitoring and Assessment for Relief and Transition (SMART) nutrition survey data of 1, 116 children from three districts and rapid nutrition assessment (RNA) data of 3, 884 children from six districts of Mozambique. We used a multiple logistic regression analysis to respond to the research question. Experiencing diarrhoea [odds ratio (OR) = 4.54; P = 0.001] was the only variable associated with acute malnutrition from the SMART survey dataset, whereas in the RNA, fever (OR = 3.0; P = 0.000) access to sanitation (OR = 0.118; P = 0.037), experiencing shock in the household (OR = 0.5; P = 0.020), diarrhoea (OR = 2.41; P = 0.001) and cough (OR = 1.75; P = 0.030) were the variables with significant association to acute malnutrition. We believe that the findings were influenced by the proportion of acute malnutrition in each survey type. Study findings confirm the association between acute malnutrition and child's health outcomes that are generally linked to poor living conditions and independent effects of shocks. This highlights the need for policy and programme to implement integrated, cross‐sectoral approaches to tackling child acute malnutrition, particularly addressing community level conditions such as water and sanitation.